Human rights and aging in two contexts : research on the elderly citizens of the City of Zagreb - Radica, Silvia (Array, 2012)
Human rights belong to everyone irrespective of age. Their protection and promotion by the government, society and the citizens is the condition sine qua non of living in dignity. Nonetheless, despite their all-encompassing nature, the rights of the elderly are still poorly codified and enforced in policies at all levels. When compared to other age cohorts, elderly people, and elderly women in particular, suffer more from poverty, social exclusion, inadequate medical care, and other forms of discrimination. This is especially true for transitional countries, including Croatia, due to underdeveloped systems of social care, the malfunctioning of social institutions and a rapid reduction in family relationships. This presentation makes a part of a pioneering study on human rights and aging in the City of Zagreb. Its main aim was to provide empirical data on the enjoyment of rights by the elderly citizens of the capital of Croatia. The results were expected to generate a wider public discussion on developing a human-rights-based policy on well-being of the elderly. The study was conducted through the application of an originally designed questionnaire on a sample of over 1000 men and women in the age of 65 and above who, at the time of the study, lived either in their homes or in welfare institutions. Some of the targeted rights were personal dignity and security ; freedom of expression, movement, and religion ; adequate standard of living ; participation in the civil, political and cultural life of the community ; information, education and training ; privacy and property. The questionnaire was structured around two composite dimensions of human rights: understanding and enjoyment. The following questions were included: are the elderly persons aware of their human rights and how do they understand them ; what are the rights which they enjoy and to what extent ; which of their rights are violated the most ; what do they see as the causes of violation of their rights ; and how do they react when their rights are violated. The results of the study confirm that knowledge and enjoyment of human rights by the elderly citizens of the City of Zagreb differ in relation to almost all independent variables. Apart from a brief review of overall results the presentation will focus on the difference in knowledge about human rights and their enjoyment between the respondents living in home and the residents of institutions for elderly care.